New control method for VSC-MTDC stations in the abnormal conditions of power system. (March 2020) - Fallah, Mehdi; Kojabadi, Hossein Madadi; Blaabjerg, Frede
Abstract: Low complexity, insensitivity on the system parameters, lesser number of electrical sensors, fast and accurate dynamic response, the ability of connection to weak AC system and high power quality are some of the major criterions for selection of control method of the voltage source converters (VSC). Considering these issues, in this paper, a new control method is presented for application in the VSC stations. This control method is based on recursive least squares with variable forgetting factor (VFF-RLS) which is a numerical estimator. Estimation of fundamental components of distorted AC grid voltage and their symmetric positive components are done by VFF-RLS estimators. Desired power injection by the proposed control method is done with corresponding to estimated signals. Simulation results in the MATLAB/SIMULINK platform and experimental results using TMS320F2812 digital signal processor validate the superiority of the proposed control method.